2014
DOI: 10.5194/acp-14-2713-2014
|View full text |Cite
|
Sign up to set email alerts
|

Dimension of aircraft exhaust plumes at cruise conditions: effect of wake vortices

Abstract: Abstract. The dispersion of aircraft emissions during the vortex phase is studied using a 3-D LES model with Lagrangian particle tracking. The simulations start with a fully rolled-up vortex pair of a type B747/A340 airplane and the tracer centred around the vortex cores. The tracer dilution and plume extent is studied for a variety of ambient and aircraft parameters until aircraft-induced effects have ceased. For typical upper tropospheric conditions, the impact of stratification is more dominant compared to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 73 publications
1
27
0
Order By: Relevance
“…The initialization of the flow field is analogous to a recent wake vortex study [ Unterstrasser et al , ]. In the latter study, wake vortex simulations with dispersing passive tracers were performed with EULAG‐LCM.…”
Section: Model Description and Setupmentioning
confidence: 99%
“…The initialization of the flow field is analogous to a recent wake vortex study [ Unterstrasser et al , ]. In the latter study, wake vortex simulations with dispersing passive tracers were performed with EULAG‐LCM.…”
Section: Model Description and Setupmentioning
confidence: 99%
“…The latter authors also compared the results obtained with Eulerian-and Lagrangian-based methods on the same computational grid and observed that the LPT allows for a more accurate representation of ice microphysics. This aspect was recently investigated by Unterstrasser et al (2014) in the context of tracer dispersion in aircraft wake vortices. They observed that LPT appears to be less dissipative than Eulerian formulations in reproducing particle dispersion in aircraft wake vortices, although the details depend on the accuracy of the numerical scheme and the computational grid.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…Other researchers have also simulated contrail lobes, confirming the essence of these results (e.g. Paugam et al ., ; Naiman et al ., ; Unterstrasser, ; Unterstrasser et al ., ; Picot et al ., ). With this large body of literature that has simulated and explained contrail lobe formation, we find it confusing that Paoli and Shariff (, p. 419) have subsequently asked, What is the mechanism of the intriguing and often‐observed mamma structures…?…”
Section: How Do Contrail Lobes Form?mentioning
confidence: 99%
“…The lobular cloud regions in contrails have been variously called ‘drop‐like formations’ and ‘pendulous lumps’ (Ludlam and Scorer, ), ‘blobs’ (Scorer and Davenport, ), ‘pendant swellings like inverted mushrooms’ (World Meteorological Organization, , p. 66), ‘pendules or fingers’ (Schaefer and Day, , p. 138), ‘puffs’ (Lewellen and Lewellen, ), ‘clumps of condensate’ (Rossow and Brown, ), ‘smoke rings’ (Unterstrasser et al, ), and ‘tear‐drop structures’ (Paoli and Shariff, ). They have also been called ‘mammatus’ (Ludlam and Scorer, ; Schultz et al, ; Unterstrasser et al, ), ‘akin to mammato‐cumulus’ (Day and Schaefer, ), and ‘mamma structures’ (Paoli and Shariff, ). This discrepancy in terminology in the literature (as well as public‐facing websites discussing contrails and meteorology) raises an important question as to what should be the appropriate scientific name for these features.…”
mentioning
confidence: 99%